Sustainable re-use of waste glass, cement and lime treated dredged material as pavement material - Gamze Bilgen; Omer Faruk Altuntas (Case Studies in Construction Materials, 2023)
The amount of waste materials such as dredged materials (DM) and waste glass (WG) have been growing exponentially since the middle of the 20th century. The most important problem created by them is the lack of space to be used for storage beside ecological, economic, and environmental problems. The purpose of the presented study is to contribute to the elimination of the mentioned problems by assessing the re-use of related wastes as pavement material. Therefore initially, DM was treated with additives at various contents that are powdered waste glass (GP) (5 %, 10 %, 15 %, 20 %, 25 %), lime (5 %) and cement (5 %). Following, a series of experimental studies and calculations such as Proctor, California bearing ratio (CBR), resilient modulus (MR) were carried out on the blends to define the geotechnical properties of them. Additionally, a cost analysis was made according to the obtained test results and the design inputs for a typical flexible pavement to determine the effect of the additives on the cost of the road construction. The underlying mechanism process of determined effects was defined by X-ray diffraction (XRD) and scanning electron microscopy (SEM). The obtained results indicate that CBR of the DM is 5.6 % which means has sufficient strength and stiffness for being used as a subgrade. Increasing the GP content in the blends contributes to achieving more desired results both geotechnically and indirectly economically. Combined use of cement and GP on DM increases the CBR value up to 83 %. This translates to an 89 % reduction in the structural number (SN) and 170 % decrease in cost index. The results of microstructural analysis indicate that the geotechnical improvement of treated DM was provided by CSH and CAH formations. Consequently, the additives used improve index and stiffness properties of DM which means a decrease in the layer thickness in road construction and therefore a decrease in the cost. The presented study confirms the usability of cement, PG, and lime-treated DM as pavement material, according to criteria specified by the Federal Highway Administration.